Digital innovation in financial services legal challenges and regulatory policy issues - Athanassiou, Phoebus (Kluwer Law International B.V., 2018)
Digital Innovation in Financial Services' is a comprehensive legal assessment of FinTech or digital financial innovation covering its potential applications to payments, securities clearing and settlement, crowd-funding, and central banking. It is the first systematic attempt at proposing a conceptual framework against which to consider the most advisable regulatory policy approach vis-à-vis this incipient phenomenon. Consumer behaviour is rapidly trending towards the use of digital devices as instruments through which to transact day-to-day business. This book shows how the global digitisation trend and the steadily rising consumer demand for innovation in the field of financial services create new opportunities not only for retail consumers but also for financial service providers, regulators, and central banks. The author offers a comprehensive overview of these opportunities and their countervailing legal and regulatory challenges.